Crowdsourced production of AI Training Data: How human workers teach self-driving cars how to see - Florian Alexander Schmidt (Hans-Böckler-Stiftung, 2019)
Since 2017 the automotive industry has developed a high demand for ground truth data. Without this data, the ambitious goal of producing fully autonomous vehicles will remain out of reach. The self-driving car depends on self-learning algorithms, which in turn have to undergo a lot of supervised training. This requires vast amounts of manual labour, performed by crowdworkers across the globe. As a consequence, the demand in training data is transforming the crowdsourcing industry. This study is an investigation into the dynamics of this shift and its impacts on the working conditions of the crowdworkers.
urn:nbn:de:101:1-2019102414513364122668
Keywords: 330; crowdworking; artificial Intelligence; self-driving cars; automotive industry; global labour markets; AI